Review of Islamic Family Law: Social Implications and Juridical Implementation in the Family Context in Indonesia - Kurniasih Fitri Maulinda; Layla Waffa Purnama; Mauna Aulia Marelyno; Mutmainah Mutmainah; Salamah Salamah; Saroh Sa’diyah; Febryan Hidayat; Abdullah Muhammad Yahya (Walidem Institute and Publishing (WIP), 2024)
Islamic family law is an important aspect of social life that has many principles and contexts in legislation and affects daily life, including marriage, divorce, and rights in the family. The methodology used in this analysis is qualitative with a descriptive-analytical literature approach, as well as a content analysis approach because it is based on Islamic legal literature. While in the complications of Islamic law, it is explained that marriage is a strong contract to obey the commands of Allah the Exalted and carry it out as a form of worship, while the meaning of marriage according to Indonesian terms here is the union of two people with different types, namely men and women who establish a bond with a covenant or contract. The hukun of marriage itself is divided into several provisions namely obligatory, sunnah, mubah, makruh, and also haram. In marriage there are also pillars including the presence of a bride and groom, the presence of a guardian and two witnesses, and the existence of ijab and qabul, in addition to harmony, marriage also has certain purposes including, marriage is recommended by the prophet Muhammad, marriage to multiply this ummah, maintain the genitals, and create peace and tranquillity in oneself. The rights and obligations that must be fulfilled by a husband to his wife are, giving dowry or dowry, providing a living mentally and mentally, and associating the wife well. In addition, a wife also has obligations to her husband that she must fulfil including, completing the husband's shortcomings (a husband and wife must complement each other), obeying the husband and it is Allah's command to follow the husband's residence after marriage, maintaining self-honour and property, devoting herself to the husband in taking care of children, and covering the disgrace of the husband. Life within the frame of marriage must be lived with full awareness, affection, and mutual respect, able to keep each other's secrets and disgraces, and can complement each other. Islam requires every marriage to last forever so that it is a married couple who can jointly manage the household and educate their children well, however, not a few realities that occur around us show examples of the fragility of the joints of a marriage which often results in the emergence of a divorce with all its consequences and access that arises.